2006
DOI: 10.2320/matertrans.47.1395
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Al<SUB>0.5</SUB>CoCrCuFeNiTi<I><SUB>x</SUB></I> (<I>x</I>=0&ndash;2.0) High-Entropy Alloys

Abstract: High-entropy Al 0:5 CoCrCuFeNiTi x alloys are synthesized using the well-developed arc-melting and casting method. The molar ratio (x) of titanium is varied from 0 to 2.0. The microstructure, hardness and wear resistance of the alloys are investigated. The alloys exhibit simple FCC, BCC, CoCr-like and Ti 2 Ni-like phases. For a small addition of titanium, the alloys form a monolithic FCC solid-solution phase. Two phases of 1 and 2 based on BCC appear at the titanium content of x ¼ 0:4 and the 1 phase becomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(68 citation statements)
references
References 9 publications
1
65
1
1
Order By: Relevance
“…3,21,[61][62][63][64][65][66][67][68][69][70][71][72][73][74] Part of the Al x CrFeCoNiCu series of alloys, which have received a great deal of attention, 1,64,73,[75][76][77][78][79][80][81][82][83][84][85][86] initial reports appeared to suggest that Al 0.5 CrFeCoNiCu was stable as a single face-centred cubic ( fcc) solid-solution phase. 3,[62][63][64]75,76,78 Subsequent studies, however, found that this not the case, and have 17,31,35,62,69,73,[85][86][87]97,107,113,125,…”
Section: Entropic Stabilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…3,21,[61][62][63][64][65][66][67][68][69][70][71][72][73][74] Part of the Al x CrFeCoNiCu series of alloys, which have received a great deal of attention, 1,64,73,[75][76][77][78][79][80][81][82][83][84][85][86] initial reports appeared to suggest that Al 0.5 CrFeCoNiCu was stable as a single face-centred cubic ( fcc) solid-solution phase. 3,[62][63][64]75,76,78 Subsequent studies, however, found that this not the case, and have 17,31,35,62,69,73,[85][86][87]97,107,113,125,…”
Section: Entropic Stabilisationmentioning
confidence: 99%
“…First, appropriate heat treatments must be selected to homogenise as-cast material, and then promote phase decomposition. Focus should be away from as-cast microstructures, which have received a great deal of attention in many HEA studies, [1][2][3]27,30,[61][62][63][64]76,79,[87][88][89][90][91]94,96,102,109,111,113,120,122,123,126,130,[133][134][135][136]141,[146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162][163]…”
Section: Entropic Stabilisationmentioning
confidence: 99%
“…[77] The hardness of Al 0.5 CoCrCuFeNiTi x alloy can be significantly increased to HV 600 or higher when x is larger than 1. [75] The hardness of Ti-containing alloys may further increase upon annealing owing to the formation of more intermetallic phases. [17,50] Addition of Mo to the system generally leads to the formation of (Cr, Mo, Co, Fe)-rich σ phase.…”
Section: Derivatives Of the Al-co-cr-cu-fe-ni Alloymentioning
confidence: 99%
“…Addition of Ti to Al-Co-Cr-Cu-Fe-Ni usually leads to formation of intermetallic phases such as the Laves phase, [15,[75][76][77][78][79] σ phase, [17,75,76] Heusler phase, [17] η-Ni 3 Ti, [17,50] and R phase. [76] This is because Ti Figure 8.…”
Section: Derivatives Of the Al-co-cr-cu-fe-ni Alloymentioning
confidence: 99%
See 1 more Smart Citation